The Effect of Acid Soaking and The Length of Sterilization on the Quality of Canned Shrimp) - Dhiah Nuraini; Novianis -; Paulus Sunarto (Warta Industri Hasil Pertanian, 1987)
A study on canning of shrimp has been conducted in order to decide the best processing stages. The effect of acid soaking of shrimp on the products has also been studied. Observation was done on pH, microbiology and acceptabitity test using 34 panelist. The result showed that 20 minutes of sterilization resulted in a sterile canned shrimp (total bacteria: 0-5 x 10^1 colony per g; coliform: 0 and anaerobic thermophilic bacteria: negative). The colour, taste and aroma of the product was acceptable, while the texture was not due to its softness.